Metro Manila My city, my home, impact of colonization, primacy of Metro Manila, urban planning and development in the face of politics - Von Einsiedel, Nathaniel author (Alliance for Safe, Sustainable, and Resilient Environments (ASSURE, Inc.), 2019)
This book tells the story of how Manila developed from a vibrant, coastal village to a global mercantile trading center from the days of the Spanish Galleons to the cosmopolitan capital it is today.